Evaluated Weights Affecting Financial Performances’ Key Factors: As Exemplified with Listed IC Design Corporations in Taiwan - Lee, Yu-Je (Asian Journal of Empirical Research, 2014)
This study aims to evaluate the weight of the key factors that influence financial performances of IC design houses listed in Taiwan. Three typical IC design houses listed in Taiwan are sampled. This paper applies Analytic Network Process (ANP) to analyze the relationship between criteria, and identify the priorities of individual criteria and the rankings of respective weights. The results suggest that the R&D capability is rated by both scholars and businesses at over 0.2 for listed IC design houses in Taiwan. Marketing innovation, intellectual capital accumulation and corporate governance are all assigned with a weighting of more than 0.1 by scholars and businesses. In other words, both scholars and businesses agree that R&D capability, marketing innovation, intellectual capital accumulation, corporate governance, and IT applications are critical to the financial performances of IC design houses listed in Taiwan. R&D capability is of particular importance. The analysis and findings can serve as a reference to the managers of IC design houses listed in Taiwan in the day-to-day business decisions and the understanding of the priority or importance of key factors to financial performances.